Post-genomic approaches to understanding interactions between fungi and their environment - R.P. de Vries; I. Benoit; G. Doehlemann; T. Kobayashi; J.K. Magnuson; E.A. Panisk; S.E. Baker; M.-H. Lebrun (IMA Fungus)
Fungi inhabit every natural and anthropogenic environment on Earth. They have highly varied life-styles including sap robes (using only dead biomass as a nutrient source), pathogens (feeding on living biomass), and symbionts (co-existing with other organisms). These distinctions are not absolute as many species employ several life styles (e.g.sap robe and opportunistic pathogen, sap robe and mycorrhizal. To efficiently survive in these different and often changing environments, fungi need to be able to modify their physiology and in some cases will even modify their local environment. Understanding the interaction between fungi and their environments has been a topic of study for many decades. However, recently these studies have reached a new dimension. The availability of fungal genomes and development of postgenomic technologies for fungi, such as transcriptomics, proteomics and metabolomics, have enabled more detailed studies into this topic resulting in new insights. Based on a Special Interest Group session held during IMC9, this paper provides examples of the recent advances in using (post- )genomic approaches to better understand fungal interactions with their environments.